A unified approach for divergent synthesis of contiguous stereodiads employing a small boronyl group - Miao Zhan (Nature Portfolio, 2020)
Predictable and unified approaches to all possible stereoisomers of acyclic compounds with contiguous stereocentres are rare. Here, the authors disclose a divergent α-functionalization of enolates with either syn or anti selectivity employing a β-boronyl group as a small, directing handle.